Teacher Talk in English Foreign Language Classroom - Reka Solita; Alamsyah Harahap; Azhar Aziz Lubis (Universitas Bengkulu, 2021)
This research investigates teacher talk in SMAN 5 Kota Bengkulu, based on FLINT theory by Moskowitz (1971). This research analyzed teacher talk categories spoken and the high frequency teacher talk used by the teacher to see what the category was often used in classroom. The design of this research was descriptive mixed-method that involved two teachers who taught at the tenth-grade of SMAN 5 Kota Bengkulu academic years 2019-20. The data of this study were taken by video recording the teacher-students interaction in the classroom that contained eleven categories of teacher talk. The data of this research were analyzed qualitatively and quantitatively. The result of this study that all of teacher’s talk categories often used by the teacher who taught at tenth-grade of SMAN 5 Kota Bengkulu during classroom interaction. The high frequency of teacher talk categories was asking question around 55.6%, while the least of teacher talk categories were correcting without rejection and criticizes student behavior. It means that the teachers tended to use indirect influence rather than direct influence.